E EFEKTIVITAS KONSENTRASI EKSTRAK BIJI MIMBA DALAM MENGENDALIKAN HAMA PADA TANAMAN DAUN BAWANG (Allium fistulosum.) - helliya, helliya_rahmianoor; Devrit, Allyanz; Battong, Umar (Universitas Medan Area, 2025)
This study aimed to determine the effectiveness of neem seed extract (Azadirachta indica) as a botanical pesticide in controlling pests on scallion (daun bawang) plants and to identify the most effective concentration. The experiment involved three extract concentrations (50 ml, 100 ml, and 150 ml per liter of water) and three application times (W1, W2, W3), with observed variables including damage intensity and the number of affected leaves. Analysis of variance showed that on day 7, the extract concentration significantly influenced pest attacks, with the 100 ml concentration (M2) being the most effective. However, on days 14 and 21, neither dosage nor application time individually showed significant effects, although the interaction between them (MxW) was statistically significant. These results suggest that the effectiveness of neem-based botanical pesticides is situational and depends on the interaction between dosage and timing. This finding can serve as a reference for developing more precise and eco-friendly pest control strategies.